Madrasah sebagai Pilihan Pendidikan - Puji Khamdani (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2015)
The existence of Madrasas as an Islamic educational institution is now placed as a school education in the National Education System. The emergence of the SKB of three ministers (Minister of Religion, Minister of Education and Culture, and Minister of Home Affairs) indicates that the existence of madrasas is already strong enough in tandem with public schools. In addition, the emergence of the three ministerial decree was also considered as a positive step for improving the quality of madrasas in terms of status, diploma and curriculum values. But then problems arose in the madrasa including madrasas having lost their historical roots, meaning that the existence of madrasas was not a continuation of pesantren and the dualism of meaning for madrasa, yaittu as public schools and pesantren with classical systems. Madrasas in the modern era have led to modern Islamic boarding school models.